1996
DOI: 10.1172/jci118918
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of human aspartyl(asparaginyl)beta-hydroxylase in hepatocellular carcinoma and cholangiocarcinoma.

Abstract: To characterize genes that become upregulated with malignant transformation of human hepatocytes, a library of monoclonal antibodies was produced against the FOCUS hepatocellular carcinoma cell line. Antibody FB-50 reacted with an antigen that was highly expressed in 4 of 10 primary hepatocellular carcinomas, in all 20 cholangiocarcinomas we studied, and in a variety of transformed cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
225
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(234 citation statements)
references
References 42 publications
9
225
0
Order By: Relevance
“…This suggests that in these transmembrane proteins, the extracellular domain regulates signal transduction by the cytoplasmic domain. 12,[24][25][26] In vivo and in vitro experiments have demonstrated that highlevel aspartyl beta-hydroxylase expression is linked to malignant transformation and invasive growth of malignant neoplasms. 27,28 It has been demonstrated that overexpression of the aspartyl beta-hydroxylase cDNAs in NIH-3T3 cells induces a transformed phenotype manifested by increased numbers of transformed foci, anchorage-independent growth, and tumorigenesis in nude mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that in these transmembrane proteins, the extracellular domain regulates signal transduction by the cytoplasmic domain. 12,[24][25][26] In vivo and in vitro experiments have demonstrated that highlevel aspartyl beta-hydroxylase expression is linked to malignant transformation and invasive growth of malignant neoplasms. 27,28 It has been demonstrated that overexpression of the aspartyl beta-hydroxylase cDNAs in NIH-3T3 cells induces a transformed phenotype manifested by increased numbers of transformed foci, anchorage-independent growth, and tumorigenesis in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the aspartyl beta-hydroxylase is overexpressed in four of 10 hepatocellular carcinomas and a number of other malignant neoplasms, including those of gastrointestinal, mammary, bronchial, pancreatic, or biliary origin, but not in most normal adult tissues. [10][11][12]28 A research showed that aspartyl betahydroxylase has an important role in regulating invasive or metastatic tumor cell growth of human cholangiocarcinoma, and that high levels of aspartyl beta-hydroxylase expression correlate with poor prognosis. 11 Our results also showed that a significantly higher tumor aspartyl beta-hydroxylase protein expression level was associated with the presence of intrahepatic metastasis and the progression of histological grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tissue inhibitors of MMP (Mohanam et al, 1995;Nakano et al, 1995) can modulate the integrity of extracellular matrix and tumor cell invasion. In this regard, the human aspartyl (asparaginyl) ␤-hydroxylase (AAH) gene is of interest because of its potential role in regulating infiltrative or metastatic growth of malignant neoplasms through ␤-hydroxylation of extracellular matrix molecules or receptors that contain the required epidermal growth factor-like domain consensus sequence (Ince et al, 1997(Ince et al, , 2000Lavaissiere et al, 1996).…”
mentioning
confidence: 99%
“…The human AAH cDNA encodes a 757-amino acid protein with a predicted M r of~86 kd (Lavaissiere et al, 1996). AAH is a member of the ␣-ketoglutarate-dependent dioxygenase family, which includes prolyl-3, prolyl-4, and lysyl hydroxylases (Jia et al, 1992;Wang et al, 1991).…”
mentioning
confidence: 99%